Supporting international medical graduates–what can be done better? A sequential explanatory mixed-methods study - Sunita Joann Rebecca Healey; Kristy Fakes; Bunmi S. Malau-Aduli; Balakrishnan R. Nair (PLoS ONE, 2025)
Background International medical graduates (IMGs) are a vital health workforce globally. Several challenges specific to IMGs warrant institutions to make necessary implementations to support their transition to working in host countries. To date, recommendations to support IMGs are frequently postulated based on challenges identified in the literature. However, there is a scarcity of information regarding IMGs’ perceptions of these supports, and how supports can be improved, from an IMG perspective. Methods A sequential explanatory mixed methods study was conducted to deeply understand how current and future supports might enhance the IMG experience. Between October and December 2023, a cross-section of IMGs across Australia were surveyed, recruited through a variety of non-random avenues. Following this, a qualitative phase comprised of interviewing participants. Findings are reported in line with Good Reporting of a Mixed Methods Study recommendations. Results In total, 192 survey participants and 36 interviewees completed the relevant ‘supports’ section of the survey and semi-structured interview respectively. By collating the results of both the survey and interviews, findings were organized into the following categories: 1) Supports experienced by IMGs in Australia- 1a) Formalised institutional or workplace support, 1b) Informal networks and community support; 2) How institutions can better support IMGs- 2a) Improve operation of bureaucratic systems, 2b) Institutions can better mobilise IMGs by supporting integration and skill development, 2c) IMGs call for changes to reduce discrimination and exploitation risks; 3) How IMGs can better support themselves- 3a) Attitude and adaptation are important, 3b) Be prepared and seek advice early, 3c) Consider life stages. Conclusions IMGs identified a range of useful current and recommended supports in and out of the workplace. In addition, IMGs have a role to play in harnessing their own agency for enhancing their own experiences in host countries. Further research and policy attention is required to ensure that institutions provide fair working conditions, support integration and prioritise cultural safety in the workplace.